2020
DOI: 10.3390/biom10030387
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin Reductase A (BVRA) Knockout in Adipocytes Induces Hypertrophy and Reduces Mitochondria in White Fat of Obese Mice

Abstract: Biliverdin reductase (BVR) is an enzymatic and signaling protein that has multifaceted roles in physiological systems. Despite the wealth of knowledge about BVR, no data exist regarding its actions in adipocytes. Here, we generated an adipose-specific deletion of biliverdin reductase-A (BVRA) (BlvraFatKO) in mice to determine the function of BVRA in adipocytes and how it may impact adipose tissue expansion. The BlvraFatKO and littermate control (BlvraFlox) mice were placed on a high-fat diet (HFD) for 12 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 78 publications
3
31
0
5
Order By: Relevance
“…The PPARα-target gene Gys2 (glycogen synthase-2) [30,37], was significantly (p < 0.05) higher in the HCR rats, but not the glucose and fat scavenger Cd36 (Figure 5C,D). We have shown that bilirubin activation of PPARα induces mitochondrial function [20], and that mice with the loss of BVRA have reduced mitochondrial function [38]. Therefore, we measured citric acid and acetic acid in the HCR and LCR rats, two metabolites associated with mitochondrial activity [39][40][41].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The PPARα-target gene Gys2 (glycogen synthase-2) [30,37], was significantly (p < 0.05) higher in the HCR rats, but not the glucose and fat scavenger Cd36 (Figure 5C,D). We have shown that bilirubin activation of PPARα induces mitochondrial function [20], and that mice with the loss of BVRA have reduced mitochondrial function [38]. Therefore, we measured citric acid and acetic acid in the HCR and LCR rats, two metabolites associated with mitochondrial activity [39][40][41].…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that HCR rats may have a higher running capacity by increasing hepatic BVRA, decreasing UGT1A1, elevating plasma bilirubin that activates PPARα for glycogen storage, and improvement of mitochondria function (Figure 7). We have shown that bilirubin activation of PPARα induces mitochondrial function [20], and that mice with the loss of BVRA have reduced mitochondrial function [38]. Therefore, we measured citric acid and acetic acid in the HCR and LCR rats, two metabolites associated with mitochondrial activity [39][40][41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…BVR-A was shown to be a Ser/Thr/Tyr kinase able to regulate a number of pathways involved in cell growth, differentiation and survival [1,3,12]. In particular, BVR-A was identified as a novel regulator of the insulin/IGF1 signaling in vitro [13][14][15] and recent studies showing that loss of BVR-A impairs insulin signaling activation and cell metabolism also in vivo support this hypothesis [16][17][18][19].…”
Section: Introductionmentioning
confidence: 96%